PERAN ORANG TUA DALAM MEMBIMBING ANAK UNTUK MELAKSANAKAN SHOLAT LIMA WAKTU (STUDI KASUS DI DUSUN KRAJAN DESA SUGIHWARAS KECAMATAN PARENGAN KABUPATEN TUBAN) - Agus Wahyudi; Mutiara Sari Dewi; Muhammad Fahmi Hidayatullah (VICRATINA, 2022)
Parents are children's primary teachers when it comes to their physical and psychological growth. Many children in the neighborhood who have reached puberty but are still unable to pray served as the inspiration for the research in this thesis. The issue addressed in this study is how parents should encourage their kids to pray five times a day in the Krajan, Tuban. This study focuses on three key questions: (1) What activities are being held for five days for children in Krajan, Tuban? (2) What part do parents play in teaching kids in Krajan, Tuban to pray five times a day? (3) What challenges do parents in Krajan, Tuban, face as they try to teach their kids to pray five times every day ?. Observation, interviews, and documentation are utilized as data gathering methods in the qualitative research methodology.  Analysis is done after the data has been gathered. The study's conclusion was that parents had played a role in teaching children to offer the five daily prayers, but not always effectively. Because they still enjoy playing and no one reminds them of prayer times, there are still many kids who do not pray five times every day.